Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 4 - Section 4.5 - Summary of Curve Sketching - 4.5 Exercises - Page 322: 32

Answer

A. The domain is $(-\infty, \infty)$ B. The y-intercept is $1$ The x-intercept is $-1$ C. The function is not an even function or an odd function. D. $\lim\limits_{x \to -\infty} \sqrt[3] {x^3+1} = -\infty$ $\lim\limits_{x \to \infty} \sqrt[3] {x^3+1} = \infty$ The line $y=x$ is a slant asymptote. E. The function is increasing on the interval $(-\infty, \infty)$ F. There is no local minimum or local maximum. G. The graph is concave down on the interval $(-1, 0)$ The graph is concave up on the intervals $(-\infty,-1)\cup (0, \infty)$ The points of inflection are $(-1,0)$ and $(0,1)$ H. We can see a sketch of the curve below.
1559061461

Work Step by Step

$y = \sqrt[3] {x^3+1}$ A. The function is defined for all real numbers. The domain is $(-\infty, \infty)$ B. When $x=0$, then $y = \sqrt[3] {0^3+1} = 1$ The y-intercept is $1$ When $y = 0$: $\sqrt[3] {x^3+1} = 0$ $x^3+1 = 0$ $x =-1$ The x-intercept is $-1$ C. The function is not an even function or an odd function. D. $\lim\limits_{x \to -\infty} \sqrt[3] {x^3+1} = -\infty$ $\lim\limits_{x \to \infty} \sqrt[3] {x^3+1} = \infty$ There are no horizontal asymptotes. $\lim\limits_{x \to -\infty} (\sqrt[3] {x^3+1}-x) = 0$ $\lim\limits_{x \to \infty} (\sqrt[3] {x^3+1}-x) = 0$ The line $y=x$ is a slant asymptote. E. We can find values of $x$ such that $y' = 0$: $y' =\frac{1}{3}(x^3+1)^{-2/3}(3x^2) = \frac{x^2}{(x^3+1)^{2/3}} = 0$ $x^2 = 0$ $x = 0$ Note that $y'$ is undefined when $x=-1$ When $x \lt -1$ or $-1 \lt x \lt 0$ or $x \gt 0$, then $y' \gt 0$ The function is increasing on the interval $(-\infty, \infty)$ F. There is no local minimum or local maximum since the function is increasing on all intervals. G. We can try to find the values of $x$ such that $y'' = 0$: $y'' =\frac{(2x)((x^3+1)^{2/3})- (x^2)(\frac{2x^2}{(x^3+1)^{1/3}})}{(x^3+1)^{4/3}}$ $y'' =\frac{(2x)(x^3+1)- (x^2)(2x^2)}{(x^3+1)^{5/3}}$ $y'' =\frac{2x}{(x^3+1)^{5/3}} = 0$ $2x = 0$ $x = 0$ Note that $y''$ is undefined when $x=-1$ When $-1 \lt x \lt 0$, then $y'' \lt 0$ The graph is concave down on the interval $(-1, 0)$ When $x \lt -1$ or $x \gt 0$, then $y'' \gt 0$ The graph is concave up on the intervals $(-\infty,-1)\cup (0, \infty)$ When $x=-1$, then $y = \sqrt[3] {(-1)^3+1} = 0$ When $x=0$, then $y = \sqrt[3] {0^3+1} = 1$ The points of inflection are $(-1,0)$ and $(0,1)$ H. We can see a sketch of the curve below.
Small 1559061461
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.